Artificial intelligence, technologies and the future of law - Mohammad, Mohammad Tahir Sabit; Ali Mohamed, Ashgar Ali; Omoola, Sodiq (CLJ Publication, 2020)
The results were used to simulate the future direction of the technology for use in local law firms and Government agencies. Accordingly, this chapter first introduces the relevant technology developed by concerned bodies for the benefit of legal search and advice, acceptance and active participation of law experts in its development. It further explains its usefulness in the discipline and then makes recommendations on the prospects of AI in Malaysia.